2018
DOI: 10.1007/s00590-018-2218-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adductor canal block and IPACK block (interspace between the popliteal artery and the capsule of the posterior knee) with adductor canal block alone after total knee arthroplasty: a prospective control trial on pain and knee function in immediate postoperative period

Abstract: ACB + IPACK is a promising technique that offers improved pain management in the immediate postoperative period without affecting the motor function around the knee joint resulting in better ROM and ambulation compared to ACB alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
130
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 19 publications
10
130
3
2
Order By: Relevance
“…Despite reporting the same results, differences have been noted in the study design, data collection periods and methodologies described. The findings from the institutional investigation show that the current article [1] accurately reports the study. Since the investigation, the article published in International Journal of Orthopaedics Sciences has been removed from the journal site; however, since this article is still accessible elsewhere, the Editor-in-Chief is publishing this Editor's Note to alert the readership and provide clarification.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Despite reporting the same results, differences have been noted in the study design, data collection periods and methodologies described. The findings from the institutional investigation show that the current article [1] accurately reports the study. Since the investigation, the article published in International Journal of Orthopaedics Sciences has been removed from the journal site; however, since this article is still accessible elsewhere, the Editor-in-Chief is publishing this Editor's Note to alert the readership and provide clarification.…”
supporting
confidence: 63%
“…The Editor-in-Chief of the European Journal of Orthopaedic Surgery and Traumatology are issuing an Editor's Note for this article [1]. It was brought to our attention that the results overlap with a previously published article by Reddy et al [2].…”
mentioning
confidence: 82%
“…1 and 2A, B), and it has been postulated to provide effective posterior knee analgesia after TKA without causing distal neurological motor deficits. [23][24][25] The purpose of this retrospective cohort study was to compare early outcomes with respect to length of stay and pain relief in patients who underwent primary TKA comparing femoral and sciatic (Fem þ Sci) combination motor nerve blocks versus the interspace between the popliteal artery and the capsule of the posterior knee and ACB (IPACK þ ACB) combination sensory nerve block.…”
mentioning
confidence: 99%
“…There are few studies published in the literature evaluating the role of IPACK in pain management after total knee arthroplasty. Sankineani et al [27] reported a significantly improved range of motion and walking distance as well as reduced visual analogue scale scores on the day of surgery for a group receiving ACB and IPACK compared with a group receiving ACB alone after total knee arthroplasty. Elliot et al [28], in a study comparing patients who received ACB and IPACK after total knee Fig.…”
Section: Discussionmentioning
confidence: 99%